In silico prediction of the enzymes involved in the degradation of the herbicide molinate by Gulosibacter molinativorax ON4T - Lopes, A. R. (2022)
Gulosibacter molinativorax ON4 T is the only known organism to produce molinate hydrolase (MolA), which catalyses the breakdown of the thiocarbamate herbicide into azepane-1-carboxylic acid (ACA) and ethanethiol. A combined genomic and transcriptomic strategy was used to fully characterize the strain ON4 T genome, particularly the molA genetic environment, to identify the potential genes encoding ACA degradation enzymes. Genomic data revealed that molA is the only catabolic gene of a novel composite transposon (Tn6311), located in a novel low copy number plasmid (pARLON1) harbouring a putative T4SS of the class FATA. pARLON1 had an ANI value of 88.2% with contig 18 from Agrococcus casei LMG 22410 T draft genome. Such results suggest that pARLON1 is related to genomic elements of other Actinobacteria, although Tn6311 was observed only in strain ON4 T. Furthermore, genomic and transcriptomic data demonstrated that the genes involved in ACA degradation are chromosomal. Based on their overexpression when growing in the presence of molinate, the enzymes potentially involved in the heterocyclic ring breakdown were predicted. Among these, the activity of a protein related to caprolactone hydrolase was demonstrated using heterologous expression. However, further studies are needed to confirm the role of the other putative enzymes.